IMPROVING THE MANAGEMENT SYSTEM OF RECYCLED PRODUCTS - Sadinov Aziz Ziyadullayevich (American Journals, 2023)
This article discusses the methods of creating necessary products from waste products and the development of innovative projects, as well as the practical application of a new mechanism for improving the automated management system, the effective illumination and involvement of digital technologies in the economic transformation of waste products into new products, and the activities of facilities based on digital technologies in the areas of waste processing processes by a technical technologist efficient organization, waste processing in the regions is to improve the work efficiency of the enterprises, as well as to support the interaction with external information systems and production processes through fully functional technologies development of material and technical base of and software interfaces of the company's resources based on digital technologies in order to separate waste products and prepare them for processing in the regions.
Keywords: waste, innovation, technology.